The Resistance to Lethal Challenge with Ostreid herpesvirus-1 of Pacific Oysters (Crassostrea gigas) Previously Exposed to This Virus - Olivia M. Liu; Paul M. Hick; Richard J. Whittington (Viruses, 2023)
Pacific oyster (Crassostrea gigas) aquaculture has been economically impacted in many countries by Pacific oyster mortality syndrome (POMS), a disease initiated by Ostreid herpesvirus 1. The objectives of this study were to determine whether naturally exposed, adult C. gigas could act as reservoirs for OsHV-1 and explain the recurrent seasonal outbreaks of POMS and to test whether or not they were resistant to OsHV-1. In a laboratory infection experiment using thermal shock, OsHV-1 replication was not reactivated within the tissues of such oysters and the virus was not transmitted to naïve cohabitating spat. The adult oysters were resistant to intramuscular injection with a lethal dose of OsHV-1 and had 118 times lower risk of mortality than naïve oysters. Considered together with the results of other studies in C. gigas, natural exposure or laboratory exposure to OsHV-1 may result in immunity during subsequent exposure events, either in the natural environment or the laboratory. While adult C. gigas can carry OsHV-1 infection for lengthy periods, reactivation of viral replication leading to mortality and transmission of the virus to naïve oysters may require specific conditions that were not present in the current experiment. Further investigation is required to evaluate the mechanisms responsible for resistance to disease in oysters previously exposed to OsHV-1, whether immunity can be exploited commercially to prevent POMS outbreaks and to determine the source of the virus for recurrent seasonal outbreaks.